Assessment of Mothers’ Awareness and Practice in the Prevention of Malnutrition among under-five years Children in Tadnum Bogoro Local Government Area of Bauchi state - Salisu, Umar Muhammad; SULEMAN AHMED WAN; Dambam, Fatima Muhammad; Muhammad Maimuna; Anas Babangida (RADINKA JOURNAL OF HEALTH SCIENCE, 2025)
The study was conducted in Tadnum Community, Bogoro Local Government Area, Bauchi State, to assess mothers’ awareness and practices in the prevention of malnutrition among under-five children. The main objective was to evaluate mothers’ awareness regarding malnutrition prevention. A descriptive survey design was used, involving 108 mothers selected through the snowball sampling technique. Data were collected using structured questionnaires and analyzed using SPSS version 29.0. Results were presented through frequency tables, percentages, means, pie charts, and standard deviations. Findings revealed that mothers had good awareness of malnutrition, as most agreed that proper nutrition during pregnancy supports fetal growth, with a mean score of 2.8. However, their preventive practices were found to be low. About 57% of mothers did not practice exclusive breastfeeding, while 54% failed to maintain a balanced diet during pregnancy. Factors hindering effective malnutrition prevention included food inaccessibility (57%) and cultural beliefs. The study recommends empowering health workers to strengthen nutrition education and support mothers in adopting good feeding practices. Promoting exclusive breastfeeding for the first six months of life and encouraging the introduction of nutritious complementary foods thereafter are essential strategies to reduce malnutrition among under-five children in the study area.